2023
DOI: 10.15252/embj.2022112030
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane topography governs the 3D dynamic localization of IgM B cell antigen receptor clusters

Abstract: B lymphocytes recognize bacterial or viral antigens via different classes of the B cell antigen receptor (BCR). Protrusive structures termed microvilli cover lymphocyte surfaces, and are thought to perform sensory functions in screening antigen-bearing surfaces.Here, we have used lattice light-sheet microscopy in combination with tailored custom-built 4D image analysis to study the cellsurface topography of B cells of the Ramos Burkitt's Lymphoma line and the spatiotemporal organization of the IgM-BCR. Ramos B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…We previously have shown that different classes of the BCR are localized together with other surface proteins inside class-specific protein nanodomains and at distinct topographic locations (24, 25). To test whether or not the IgM-BCR or IgG1-BCR Ramos B cells differ in the expression of other B cell surface proteins we stained these cells with antibodies directed against 29 different B cell surface markers.…”
Section: Resultsmentioning
confidence: 99%
“…We previously have shown that different classes of the BCR are localized together with other surface proteins inside class-specific protein nanodomains and at distinct topographic locations (24, 25). To test whether or not the IgM-BCR or IgG1-BCR Ramos B cells differ in the expression of other B cell surface proteins we stained these cells with antibodies directed against 29 different B cell surface markers.…”
Section: Resultsmentioning
confidence: 99%
“…30 For example, B cell receptors (BCRs) are also clustered. 31 In the periphery pre-secreted natural antibodies could compete with them for reaction with antigens. More antigen would be required to produce a given effect.…”
Section: Selectionmentioning
confidence: 99%
“…Thus, the antigen dose‐response requirements for these anatomically separate processes, while perhaps having fundament similarities, would likely cover different ranges 30 . For example, B cell receptors (BCRs) are also clustered 31 . In the periphery pre‐secreted natural antibodies could compete with them for reaction with antigens.…”
Section: Positive Repertoire Selectionmentioning
confidence: 99%
“…6 Similar role of microvilli was described or predicted for other immune cells. [7][8][9] Nanotechnology introduced a variety of objects with feasible sizes and functional advantages to mimic the geometry of microvilli. 10 Nanoparticles are broadly available in a variety of compositions, sizes and surface functionalization.…”
Section: Introductionmentioning
confidence: 99%